Morphometric characterization of intermittent natural lagoons in the Seridó Region, Rio Grande do Norte State, Brazil: a preliminary analysis - Medeiros, Débora de Macêdo; da Silva Costa, Diógenes Felix; de Azevedo, Silvana Barbosa; de Medeiros Costa, Augusto César (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2023)
This study presents a morphometric analysis of margin natural ponds in Seridó Natal region in the Brazilian semiarid region. The semiarid ponds are very important for the region, since that provided important ecosystems services as habitats of various species, is one of the water supply sources, and harbor a great biodiversity. The study aimed to analyze the standard morphometric its banks. In the methodology was based on digital image processing and classification and quantification of classes per hectare, using the index F. Á study area presented a total of 53 natural lakes, corresponding to a total area of 228.3 ha, where all had similar shapes (circular/oval). Classes were established by size in hectare, this measure was performed using the standard deviation calculation, setting the maximum value of 30% for each class, with that weredivided into six classes intervals. The study of the morphology of the continental lakes in the area in question contributes towards a better understanding of the variability of morphometric characteristics of these important continental aquatic systems in a region so lacking in water resources for most of the time.
Keywords: Semiarid; F index; Morphometric standard and oval circular